1999
DOI: 10.1523/jneurosci.19-15-06318.1999
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Ensembles: The Role of Neuropeptide Structures in Receptor Binding

Abstract: Conformational properties of several similar FMRFamide-like neuropeptides from mollusks were investigated by nuclear magnetic resonance (NMR) spectroscopy. It was found that amino acid substitutions in the N-terminal variable regions of the peptides had dramatic effects on the populations of reverse turns in solution. The populations of turns, as measured by two independent NMR parameters, were found to be highly correlated (r(2) = 0.93 and 0. 82) with IC(50) values using receptor membrane preparations from He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…Moreover, the N-terminal sequences of agonists appeared to be very important for MrgA1 activation. It has been known that C-terminally amidated peptides can take a variety of conformations depending on the amino acids at the N terminus (26). Thus, assuming that the ligand for the Mrg family is a RFa-related peptide, the combination of amidation and N-terminal sequences may be sufficient to generate differences in ligand conformation unique for each Mrg receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the N-terminal sequences of agonists appeared to be very important for MrgA1 activation. It has been known that C-terminally amidated peptides can take a variety of conformations depending on the amino acids at the N terminus (26). Thus, assuming that the ligand for the Mrg family is a RFa-related peptide, the combination of amidation and N-terminal sequences may be sufficient to generate differences in ligand conformation unique for each Mrg receptor.…”
Section: Discussionmentioning
confidence: 99%
“…45 Studies on G-protein-coupled peptide receptors showed by NMR and receptor binding assays that the ligand's amide moiety is a key binding determinant. 46,47 The most frequently annotated C-terminal modification reported in TopFIND is Cmethyl-esterification; however only 17 instances are reported in man, 6 in mouse and 7 in yeast. 13 Only one of C-terminal modification has been studied experimentally-the methylation of the C-terminal leucine in the catalytic subunit of phosphoprotein phosphatase 2A (PP2A), which is required for the interaction with its regulatory subunit and is involved in modulating neural plasticity.…”
Section: C-terminal Modificationsmentioning
confidence: 99%
“…In such a case, N-terminally extended forms may affect receptor binding, but do not abolish it. For example, FMRFamide peptides can exist in many extended forms in some prohormones; many overlap with regard to receptor binding, and they may have overlapping or distinct functions (42,43). Peptides can be detected and tested, but without appropriate controls (such as sampling the peptides released after appropriate physiological stimulations), the data obtained might be misleading.…”
Section: Brain Peptides Versus Signaling Peptidesmentioning
confidence: 99%